Taking into Account the Physical and Mechanical Properties of Clay Soils in Engineering Geological Exploration Calculations - Mustanov Ilg‘orjon Shokir o‘g‘li; Parmanov Murodqosim Nodir o‘g‘li (Scientific Trends, 2025)
In the proposed work, a nonlinear dependence is given, which makes it possible to determine the limiting value of the forces on the pile at a given value of the permissible settlement outside the proportionality limits, and also shows the real possibility of using nonlinear properties of deformation of clay soils in engineering calculations.
Keywords: Loading path, shear stresses, settlement, nonlinear properties, piles, vertical displacements, angular deformation.